Preparation method and application of novel ruthenium-based catalyst
By loading metal Ru on the Al2O3 support, the new Al2O3 supported Ru-based catalyst was prepared, which solved the problem of high ruthenium content in the existing catalysts, and achieved efficient catalytic formation of cyclohexene under low precious metal loads, reducing production costs.
Patent Information
- Application Number
- CN202411771997.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-04
AI Technical Summary
Among the existing catalysts for the hydrogenation of benzene partially, the content of ruthenium (Ru) is high, resulting in excessive catalyst cost, and the ruthenium content needs to be reduced to improve cost advantages.
Using the new Al2O3-supported Ru-based catalyst, the Ru loading is controlled between 0.5 wt% and 5.0 wt% by loading metal Ru on the Al2O3 support, and the proportion of pores with pore diameters of 2 nm to 50 nm accounts for more than 50%.
The catalytic activity of 50-80 at a lower precious metal load is achieved, reducing the catalyst production cost and increasing the yield of cyclohexene.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and particularly relates to a preparation method of a novel ruthenium-based catalyst and application of the catalyst in the reaction of partially hydrogenating benzene to produce cyclohexene. Background Art
[0002] Cyclohexene has an active C=C double bond and is an important chemical raw material. As an intermediate, it is widely used in the production of fine chemicals such as medicines, pesticides, dyes and polyesters. In industry, the main methods for producing cyclohexene include cyclohexanol dehydration, cyclohexane dehydrohalogenation, cyclohexane dehydrogenation and partial hydrogenation of benzene. Among them, the partial hydrogenation of benzene to cyclohexene has the advantages of easy availability of raw material benzene, low price, simple reaction process and easy operation, making it the most commonly used method for cyclohexene production. However, in the partial hydrogenation of benzene, the standard Gibbs free energy change (-98 kJ / mol) of the formation of cyclohexane is much smaller than the standard Gibbs free energy change (-23 kJ / mol) of the formation of cyclohexene in thermodynamics. Therefore, partial hydrogenation of benzene is more likely to produce cyclohexane in thermodynamics, and it is necessary to select appropriate catalysts and reaction systems to increase the yield of cyclohexene.
[0003] At present, RuZn catalyst is commonly used in the partial hydrogenation of benzene to produce cyclohexene in industry. Among them, the Ru content reaches 90 wt%~95wt%. Ru is a precious metal, and the current market price is about 100 yuan / gram. A higher Ru content will inevitably lead to excessive catalyst cost, thereby increasing the production cost of cyclohexene. Therefore, reducing the Ru content is an effective means to improve the cost advantage of the catalyst. For low ruthenium catalysts, various strategies have been proposed before. For example, CN116196938A loads metal Ru on ZrO2 and adds auxiliary agent Cu, and can obtain a cyclohexene yield of nearly 40 mol% when the Ru content is less than 5 wt%, and can continuously produce cyclohexene in a fixed bed reactor. CN117899858A uses a Ti-Si composite material as a carrier to load metal Ru, and uses the hydrophilicity of the carrier to obtain a cyclohexene yield of nearly 50 mol% when the Ru content is less than 5 wt%. In addition, CN108409520B removes Zn from the RuZn catalyst supported by ZrO2 by alkali treatment, and can obtain a higher cyclohexene yield under low Ru conditions. CN106140154B can obtain a similar effect by changing the pore size distribution of the ZrO2 carrier so that most of its pore sizes are distributed above 15 nm.
[0004] For the reaction of partial hydrogenation of benzene to produce cyclohexene, patents such as CN103787816B, CN103785378B, and CN103785382B add solvent ethanol, water, and auxiliary agent Zn to the reaction system to achieve the preparation of cyclohexene in a fixed bed reactor; patents such as CN117718043A and CN117816157A add hydrotalcite and C 60 By introducing Ru-based catalysts and changing the hydrophilicity and electronic effect of the catalyst surface, efficient catalytic production of cyclohexene can be achieved in a fixed bed reactor. Summary of the invention
[0005] The present invention aims to provide a novel ruthenium-based catalyst and a preparation method thereof, as well as an application in the reaction of preparing cyclohexene by partial hydrogenation of benzene. Compared with the common ZrO2-supported Ru-based catalyst, the present invention provides a novel Al2O3-supported Ru-based catalyst, which has the advantages of low metal Ru content, low catalyst cost and high cyclohexene yield, and has cost advantages in large-scale industrial applications.
[0006] A novel ruthenium-based catalyst is Ru-Al2O3 prepared by loading metallic ruthenium onto an Al2O3 carrier, wherein the proportion of pores with a pore size of 2 nm to 50 nm to the pore size of 2 nm to 150 nm is greater than 50%, and the Ru loading amount is 0.5 wt% to 5.0 wt%.
[0007] A method for preparing a novel ruthenium-based catalyst comprises the following steps: (1) Preparation of Al2O3 carrier: dissolving Al salt, precipitant and surfactant in water and reacting to obtain Al2O3 carrier; (2) Disperse the Al2O3 carrier in water, add Ru salt while stirring, and after it is completely dissolved, add the reducing agent and continue stirring. Finally, filter and dry to obtain Ru-Al2O3.
[0008] The surfactant in step (1) is one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, sodium hexadecyl sulfonate, sodium oleate or polyethylene glycol.
[0009] The precipitant in step (1) is urea or mixed alkali solution; The mixed alkali solution is a mixture of Na2CO3 and NaOH.
[0010] The Al salt in step (1) is Al(NO3)3·9H2O; the Ru salt in step (2) is RuCl3; the reducing agent in step (2) is one or more of hydrazine hydrate, potassium borohydride or formaldehyde.
[0011] When the precipitant is urea, the specific steps for preparing the Al2O3 carrier are: Dissolve Al salt, urea and surfactant in water in turn, stir for 2-3 hours, hydrothermally react at 80-120°C for 20-30 hours, filter and dry, and finally calcine at 500-800°C for 4-6 hours to obtain an Al2O3 carrier.
[0012] When the precipitant is a mixture of Na2CO3 and NaOH, the specific steps for preparing the Al2O3 carrier are: S1. Dissolve Al salt in water to make Al 3+ Liquid metal; dissolve Na2CO3 and NaOH in water to prepare a mixed alkali solution; dissolve a surfactant in water to prepare a surfactant aqueous solution; S2. Under vigorous stirring, the Al 3+ The metal liquid and the mixed alkali solution are simultaneously dripped into the surfactant aqueous solution to control the pH of the system to be 8.5-11.0; S3. After the titration is completed, the solution containing the precipitate obtained in S2 is aged at 80-90°C for 10-14 hours, and then filtered and dried to obtain alumina; The molar ratio of Na2CO3 to NaOH is 1:2-4.
[0013] The Al2O3 carrier prepared in step (1) has pores with a pore size of 2 nm to 50 nm accounting for more than 50% of the pore size of 2 nm to 150 nm, and a total pore volume of 0.6 cm 3 / g~1.5 cm 3 / g, with a specific surface area of 200 m 2 / g~500 m 2 / g; The metal Ru loading in the Ru-Al2O3 prepared in step (2) is 0.5 wt%~5.0 wt%; The average particle size of Ru in the Ru-Al2O3 prepared in step (2) is less than 10 nm; In the Ru-Al2O3 prepared in step (2), the proportion of pores with a pore size of 2 nm to 50 nm to pores with a pore size of 2 nm to 150 nm is greater than 50%.
[0014] Application of a new ruthenium-based catalyst for partial hydrogenation of benzene to cyclohexene.
[0015] The beneficial effects of the present invention are: Compared with the prior art, the catalyst of the present invention has higher catalytic activity. By using the catalyst of the present invention, the catalyst can reach 50-80 (i.e., 50% conversion rate and 80% cyclohexene selectivity) with a lower noble metal loading under the same catalyst usage amount. This will greatly reduce the catalytic production cost while improving the cyclohexene production efficiency, providing certain possibilities for subsequent industrial applications. In addition, the catalytic activity is mainly due to the presence of a large number of pores below 50 nm in the pores of alumina, which provides a certain confinement effect, produces local benzene-rich and cyclohexene-poor conditions at the microscopic level, and changes the electronic properties of the metal ruthenium surface. DETAILED DESCRIPTION
[0016] The embodiments of the present invention will be described in detail below with reference to examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.
[0017] The present invention provides a method for preparing a novel ruthenium-based catalyst and its application in the reaction of preparing cyclohexene by partial hydrogenation of benzene. In the present invention, the catalytic performance evaluation device used is a kettle reactor, which is similar to the production device of preparing cyclohexene by partial hydrogenation of benzene in industrial production.
[0018] In the present invention, unless otherwise specified, the reaction conditions for partial hydrogenation of benzene to produce cyclohexene are: 5.0 MPa, 140°C, rotation speed 1000 r / min, catalyst 1 g, benzene 50 mL, water 100 mL, 2 g ZnSO4.
[0019] In the present invention, unless otherwise specified, the benzene conversion rate and cyclohexene selectivity listed in Table 1 are obtained under the condition that the benzene conversion rate is about 50%.
[0020] To further illustrate the present invention, the following embodiments are described in detail, but the protection scope of the present invention is not limited to the following embodiments.
[0021] Example 1 Weigh 60 g Al(NO3)3·9H2O and dissolve it in deionized water. Add 10 g urea. After it is completely dissolved, add 6 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123). After vigorous stirring for 3 h, put it into a hydrothermal kettle, hydrotherm at 120 °C for 24 h, filter, dry, and finally calcine at 600 °C for 5 h to obtain alumina. The physical adsorption test results show that the specific surface area of the alumina sample is 289 m 2 / g, with a total pore volume of 1.4 cm 3 / g, the average pore size is 23 nm, and the proportion of pores with a pore size of 2nm~50nm accounts for 61% of the pore size of 2nm~150nm.
[0022] Weigh 20 g of the above alumina carrier, grind it into powder, disperse it in deionized water, add 0.9 g RuCl3, stir at 80℃ for 3 h, add 1.1 g KBH3, stir for 1 h, filter until there is no Cl ion in the filtrate, and dry it to obtain the Ru-Al2O3 sample. The loading amount of metal Ru is 1.75 wt%. The physical adsorption test results show that the proportion of pores with a pore size of 2 nm~50 nm in the catalyst sample is 58% of the pore size of 2 nm~150 nm. TEM characterization results show that the average particle size of metal Ru is 3.8 nm.
[0023] Example 2 Weigh 30 g Al(NO3)3·9H2O and dissolve it in deionized water to prepare Al 3+ The metal liquid has a concentration of 1.0 mol / L, and then a mixed alkali solution with a Na2CO3 concentration of 0.5 mol / L and a NaOH concentration of 1.6 mol / L is prepared. The double titration method is used to simultaneously drop the metal liquid and the alkali solution into 200 ml of deionized water containing 5 g of polyethylene glycol under vigorous stirring. The pH of the mixed solution is maintained at 10.0±0.5 by controlling the alkali solution speed. After the titration is completed (the precipitation no longer increases after the metal liquid is added), the solution containing the precipitate is aged at 80 °C for 12 h, and then filtered until the filtrate is neutral. Finally, after drying, the obtained sample is the alumina carrier. The physical adsorption test results show that the specific surface area of the alumina sample is 345 m 2 / g, and the total pore volume is 1.2 cm 3 / g, the average pore size is 20 nm, and the proportion of pores with a pore size of 2 nm~50 nm accounts for 69% of the pore size of 2 nm~150 nm.
[0024] Metal Ru was loaded on the Al2O3 carrier with reference to Example 1. The loading amount of metal Ru was 1.75 wt%. The physical adsorption test results showed that the proportion of pores with a pore size of 2 nm to 50 nm in the catalyst sample accounted for 65% of the pore size of 2 nm to 150 nm. TEM characterization results showed that the average particle size of metal Ru was 2.5 nm.
[0025] Example 3 20 g of commercial Al2O3 carrier (Yichang Supeng Technology Co., Ltd., model A06) was weighed and calcined at 600 °C for 5 h before being used as a catalyst carrier. The physical adsorption test results showed that the specific surface area of the alumina sample was 223 m 2 / g, and the total pore volume is 1.2 cm 3 / g, the average pore size is 29 nm, and the proportion of pores with a pore size of 2 nm~50 nm accounts for 54% of the pore size of 2 nm~150 nm.
[0026] Metal Ru was loaded on the Al2O3 carrier with reference to Example 1. The loading amount of metal Ru was 1.75 wt%. The physical adsorption test results showed that the proportion of pores with a pore size of 2 nm to 50 nm in the catalyst sample accounted for 50% of the pore size of 2 nm to 150 nm. TEM characterization results showed that the average particle size of metal Ru was 3.0 nm.
[0027] Example 4 The Al2O3 carrier was prepared by referring to Example 1. The difference from Example 1 is that the hydrothermal temperature in this example is 80 °C. The physical adsorption test results show that the specific surface area of the alumina sample is 182 m 2 / g, total pore volume 1.0cm 3 / g, the average pore size is 24 nm, and the proportion of pores with a pore size of 2 nm~50 nm accounts for 56% of the pore size of 2 nm~150 nm.
[0028] Metal Ru was loaded on the Al2O3 carrier with reference to Example 1. The loading amount of metal Ru was 1.75 wt%. The physical adsorption test results showed that the proportion of pores with a pore size of 2 nm to 50 nm in the catalyst sample accounted for 51% of the pore size of 2 nm to 150 nm. TEM characterization results showed that the average particle size of metal Ru was 4.2 nm.
[0029] Example 5 The Al2O3 carrier was prepared by referring to Example 2. The difference from Example 2 is that the surfactant in this example is P123, and the addition amount is 5 g. The physical adsorption test results show that the specific surface area of the alumina sample is 375 m 2 / g, with a total pore volume of 1.2 cm 3 / g, the average pore size is 24nm, and the proportion of pores with a pore size of 2 nm~50 nm accounts for 73% of the pore size of 2 nm~150 nm.
[0030] Metal Ru was loaded on the Al2O3 carrier with reference to Example 1. The loading amount of metal Ru was 1.75 wt%. The physical adsorption test results showed that the proportion of pores with a pore size of 2 nm to 50 nm in the catalyst sample accounted for 70% of the pore size of 2 nm to 150 nm. TEM characterization results showed that the average particle size of metal Ru was 3.2 nm.
[0031] Example 6 The Al2O3 carrier was prepared by referring to Example 2. The difference from Example 2 is that the pH of the mixed solution in this example is maintained at 9.0±0.5. The physical adsorption test results show that the specific surface area of the alumina sample is 290m 2 / g, and the total pore volume is 1.3 cm3 / g, the average pore size is 28 nm, and the proportion of pores with a pore size of 2 nm~50 nm accounts for 62% of the pore size of 2 nm~150 nm.
[0032] Metal Ru was loaded on the Al2O3 carrier with reference to Example 1. The loading amount of metal Ru was 1.75 wt%. The physical adsorption test results showed that the proportion of pores with a pore size of 2 nm to 50 nm in the catalyst sample accounted for 57% of the pore size of 2 nm to 150 nm. TEM characterization results showed that the average particle size of metal Ru was 2.7 nm.
[0033] Example 7 Ru-Al2O3 was prepared with reference to Example 2. The difference from Example 2 is that the reducing agent in this example is 50% hydrazine hydrate, and the addition amount is 5 ml. The loading amount of metal Ru is 1.75wt%. The physical adsorption test results show that the proportion of pores with a pore size of 2nm~50nm in the catalyst sample accounts for 51% of the pore size of 2nm~150nm. The TEM characterization results show that the average particle size of metal Ru is 3.3nm.
[0034] Example 8 Ru-Al2O3 was prepared with reference to Example 2. The difference from Example 2 is that the loading amount of metal Ru in this example is 5.0 wt%. The physical adsorption test results show that the proportion of pores with a pore size of 2 nm to 50 nm in the catalyst sample accounts for 60% of the pore size of 2 nm to 150 nm. The TEM characterization results show that the average particle size of metal Ru is 4.3 nm.
[0035] Comparative Example 1 The Al2O3 carrier was prepared according to Example 1. The difference from Example 1 is that no surfactant was added and the hydrothermal temperature was 80 °C. The physical adsorption test results showed that the specific surface area of the alumina sample was 219 m 2 / g, and the total pore volume is 1.1 cm 3 / g, the average pore size is 30 nm, and the proportion of pores with a pore size of 2 nm~50 nm accounts for 38% of the pore size of 2 nm~150 nm.
[0036] Metal Ru was loaded on the Al2O3 carrier with reference to Example 1. The loading amount of metal Ru was 1.75 wt%. The physical adsorption test results showed that the proportion of pores with a pore size of 2 nm to 50 nm in the catalyst sample accounted for 31% of the pore size of 2 nm to 150 nm. TEM characterization results showed that the average particle size of metal Ru was 4.1 nm.
[0037] Comparative Example 2 Weigh 30 g Al(NO3)3·9H2O and dissolve it in deionized water to prepare Al 3+ Prepare a 1.0 mol / L metal liquid and a 1.0 mol / L NaOH alkali solution. Use the double titration method to drip the metal solution and alkali solution into deionized water at the same time. During the titration process, maintain vigorous stirring and control the alkali solution speed to keep the pH of the mixed solution at 10.0±0.5. After the titration is completed, age the solution containing the precipitate at 80°C for 12 h, then filter it until the filtrate is neutral, and finally dry it to obtain the alumina carrier. The physical adsorption test results show that the specific surface area of the alumina sample is 245m 2 / g, and the total pore volume is 1.1 cm 3 / g, the average pore size is 40 nm, and the proportion of pores with a pore size of 2 nm~50 nm accounts for 40% of the pore size of 2 nm~150 nm.
[0038] Metal Ru was loaded on the Al2O3 carrier with reference to Example 1. The loading amount of metal Ru was 1.75 wt%. The physical adsorption test results showed that the proportion of pores with a pore size of 2 nm to 50 nm in the catalyst sample accounted for 34% of the pore size of 2 nm to 150 nm. TEM characterization results showed that the average particle size of metal Ru was 3.9 nm.
[0039] The above samples were subjected to partial hydrogenation activity evaluation of benzene. The evaluation conditions were as described above. The catalytic activity test results are listed in Table 1.
[0040] Table 1 Performance results of the catalysts prepared in the examples and comparative examples for partial hydrogenation of benzene
[0041] From the above results, it can be seen that pores with a diameter of 2 nm to 50 nm are conducive to the formation of cyclohexene. This is mainly due to the presence of a large number of mesopores below 50 nm in the pores of alumina, which provide a certain confinement effect, produce local conditions of rich benzene and less cyclohexene at the microscopic level, and change the electronic properties of the metal ruthenium surface, so that it can reach 50-80 (i.e., 50% conversion rate, 80% cyclohexene selectivity) with a lower noble metal loading.
Claims
1. A novel ruthenium-based catalyst, characterized in that: Ru-Al2O3 is prepared by loading metallic ruthenium onto an Al2O3 carrier, the proportion of pores with a pore size of 2 nm~50 nm to pores with a pore size of 2 nm~150 nm is greater than 50%, and the Ru loading amount is 0.5 wt%~5.0wt%.
2. A method for preparing a novel ruthenium-based catalyst, characterized in that: The following steps are involved: (1) Preparation of Al2O3 carrier: dissolving Al salt, precipitant and surfactant in water and reacting to obtain Al2O3 carrier; (2) Disperse the Al2O3 carrier in water, add Ru salt while stirring, and after it is completely dissolved, add the reducing agent and continue stirring. Finally, filter and dry to obtain Ru-Al2O3.
3. The method for preparing a novel ruthenium-based catalyst according to claim 2, characterized in that: The surfactant in step (1) is one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, sodium hexadecyl sulfonate, sodium oleate or polyethylene glycol.
4. The method for preparing a novel ruthenium-based catalyst according to claim 2, characterized in that: The precipitant in step (1) is urea or mixed alkali solution; The mixed alkali solution is a mixture of Na2CO3 and NaOH.
5. The method for preparing a novel ruthenium-based catalyst according to claim 2, characterized in that: The Al salt in step (1) is Al(NO3)3·9H2O; the Ru salt in step (2) is RuCl3; the reducing agent in step (2) is one or more of hydrazine hydrate, potassium borohydride or formaldehyde.
6. The method for preparing a novel ruthenium-based catalyst according to claim 4, characterized in that: When the precipitant is urea, the specific steps for preparing the Al2O3 carrier are: Dissolve Al salt, urea and surfactant in water in turn, stir for 2-3 hours, hydrothermally react at 80-120°C for 20-30 hours, filter and dry, and finally calcine at 500-800°C for 4-6 hours to obtain an Al2O3 carrier.
7. The method for preparing a novel ruthenium-based catalyst according to claim 4, characterized in that: When the precipitant is a mixture of Na2CO3 and NaOH, the specific steps for preparing the Al2O3 carrier are: S1. Dissolve Al salt in water to make Al 3+ Liquid metal; dissolve Na2CO3 and NaOH in water to prepare a mixed alkali solution; dissolve a surfactant in water to prepare a surfactant aqueous solution; S2. Under vigorous stirring, the Al 3+ The metal liquid and the mixed alkali solution are simultaneously dripped into the surfactant aqueous solution to control the pH of the system to be 8.5-11.0; S3. After the titration is completed, the solution containing the precipitate obtained in S2 is aged at 80-90°C for 10-14 hours, and then filtered and dried to obtain alumina; The molar ratio of Na2CO3 to NaOH is 1:2-4.
8. The method for preparing a novel ruthenium-based catalyst according to claim 2, characterized in that: The Al2O3 carrier prepared in step (1) has pores with a pore size of 2 nm to 50 nm accounting for more than 50% of pores with a pore size of 2 nm to 150 nm, and a total pore volume of 0.6 cm 3 / g~1.5 cm 3 / g, with a specific surface area of 200 m 2 / g~500 m 2 / g; The metal Ru loading in the Ru-Al2O3 prepared in step (2) is 0.5 wt%~5.0 wt%; The average particle size of Ru in the Ru-Al2O3 prepared in step (2) is less than 10 nm; In the Ru-Al2O3 prepared in step (2), the proportion of pores with a pore size of 2 nm to 50 nm to pores with a pore size of 2 nm to 150 nm is greater than 50%.
9. Application of a novel ruthenium-based catalyst, characterized in that: Used for partial hydrogenation of benzene to produce cyclohexene.
Citation Information
Patent Citations
Catalyst for preparing cyclohexene by partial hydrogenation of benzene and its preparation method and application
CN103785378B
A kind of highly stable benzene hydrogenation cyclohexene catalyst and its preparation method and application
CN103785382B
Cyclohexene preparation process by partial hydrogenation of benzene
CN103787816B
A catalyst for the selective hydrogenation of benzene to cyclohexene, its preparation method and application
CN106140154B
Method for treating catalyst precursor for preparing cyclohexene by hydrogenation of benzene, method for preparing catalyst, and method for preparing cyclohexene by hydrogenation of benzene
CN108409520B